KONSEP SISTEM INFORMASI RENCANA TATA RUANG WILAYAH UNTUK KABUPATEN/KOTA DI INDONESIA - Imam Buchori (Diponegoro University, 2011)
This paperaims at discussing a concept of Spatial Information for Regional Planningthat can beapplied at Indonesian district (kabupaten/kota) level. The discussionisdivided into the following substances: abasic concept of Geographic InformationSystem (GIS)-based Spatial InformationSystem for Regional Planning (SISRP); kinds of data for the SISRP-model; potential users of the SIRP-model; GIS components as the media for presentinginformationin the SISRP-model; the SISRP-model towards participatory planningconcepts; andimplementationaspects of the SISRP-model and a short review of SISRP-development in two Kabupatens, i.e. Rembang and Pemalang. In the end of this paper, a summaryresulted from the discussion and some recommendationsconcerning the potentials and bariers of SISRP-development in Indonesia aregiven.